PENGARUH BRAND AMBASSADOR GIRL GROUP KOREA TWICE TERHADAP BRAND IMAGE SCARLETT WHITENING - Muhammad Zikri Hidayat; Kresno Yulianto (Transpublika Publisher, 2025)
According to kompas.co.id, Scarlett Whitening ranks second in the category of local skincare products in Indonesia. To improve brand image, Scarlett Whitening collaborates with girl group TWICE as brand ambassador. This study aims to analyze the influence of TWICE brand ambassadors on Scarlett Whitening's brand image. Using the positivism paradigm and quantitative approach, data was collected through a survey using the Taro Yamane method, involving 100 respondents from Sukmajaya, Depok, who knew TWICE's brand ambassador and used Scarlett Whitening. The sample was selected using purposive sampling technique (non-probability). Data were analyzed with simple linear regression test using SPSS. The results showed that TWICE brand ambassadors have a positive influence on Scarlett Whitening's brand image. The linear test results in a significance value (Sig) <0.01, indicating a significant relationship. The regression coefficient of the brand ambassador variable (X) of 0.449 shows a positive influence. The t value of 8.991 with Sig 0.01 <0.05 confirms that TWICE brand ambassadors have a significant effect on Scarlett Whitening brand image.